-3+32-7x=-2(5x+1)

Simple and best practice solution for -3+32-7x=-2(5x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3+32-7x=-2(5x+1) equation:


Simplifying
-3 + 32 + -7x = -2(5x + 1)

Combine like terms: -3 + 32 = 29
29 + -7x = -2(5x + 1)

Reorder the terms:
29 + -7x = -2(1 + 5x)
29 + -7x = (1 * -2 + 5x * -2)
29 + -7x = (-2 + -10x)

Solving
29 + -7x = -2 + -10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10x' to each side of the equation.
29 + -7x + 10x = -2 + -10x + 10x

Combine like terms: -7x + 10x = 3x
29 + 3x = -2 + -10x + 10x

Combine like terms: -10x + 10x = 0
29 + 3x = -2 + 0
29 + 3x = -2

Add '-29' to each side of the equation.
29 + -29 + 3x = -2 + -29

Combine like terms: 29 + -29 = 0
0 + 3x = -2 + -29
3x = -2 + -29

Combine like terms: -2 + -29 = -31
3x = -31

Divide each side by '3'.
x = -10.33333333

Simplifying
x = -10.33333333

See similar equations:

| 2x=4-9x | | 5x-7+10x+9= | | x*88(5+0.77)-2.4=57 | | m+34=19 | | 2x^2+6x=7x+5 | | x^2+16x=-162 | | 5c=15c-60 | | x^2+ax+4a+2=0 | | 9+(x+3y)i=x+6i | | sqrt(x^2-15)-4=0 | | (3x-1)(9x^2-6x+1)= | | y=20-35(-10) | | sqrt(x^2-14)-4=0 | | 8x=5x-6 | | 3x+5+86.8=180 | | 9x^2+36x-35=0 | | -2(y-5)=26 | | 20v+28=v+47 | | W^2=20x | | 2x+8+5x=-19 | | f(-2.2)=[x]+3 | | 2a+13b-2a+2b+25= | | 64=X+10+y | | 3x+5=-27 | | x-5y=-154 | | 3(2X+25)-2(z-1)=78 | | 4(x+9)+3=4x+7 | | f(2.75)=x+1 | | -34-4x=23-x | | -0.7-0.6=-0.2y+3.4 | | 10x+20+20y= | | x-12y=-158-x |

Equations solver categories